Geochemical and petrographic assessment of clay outcrops and archaeological ceramics from the pre-Hispanic site of Aguas Buenas (cal 400–1250 CE), central Nicaragua - Casale, Simone; Donner, Natalia; Braekmans, Dennis; Geurds, Alexander (Elsevier, 2020)
This research characterizes and reconstructs clay procurement and production practices through the integration of in-situ portable XRF and petrographic analysis on ancient ceramics and clay materials recovered from the Mayales river subbasin (central Nicaragua). A particular choice for this study was the largest and arguably most significant archaeological site in the area, Aguas Buenas (cal 400–1250 CE), a pre-Hispanic indigenous agglomeration consisting of 371 human-made mounds of various shapes arranged in geometric patterns. Microanalytical approaches were applied to reconstruct the use of raw mineral resources in the production of ubiquitous pottery materials found at this site and in its immediate surroundings. The resulting compositional analysis produced geochemical and mineralogical data allowing for the characterisation of distinct, geologically-based compositional groups throughout the valley, improving on the limited geological data resolution previously available. The integrated microscopic and compositional analysis (through p-XRF) of archaeological pottery materials and raw clay samples, generates a number of hypotheses and insights about the nature of the Aguas Buenas site, and its role as a shared space amongst groups living in the Mayales river Subbasin. Additionally, this study provides a solid research framework of investigation that can be employed for more detailed and extensive future studies on pre-Hispanic human occupation in this research area or elsewhere.
Keywords: Archaeological provenance; Pre-Hispanic Nicaragua; Petrography; Ceramic microstructure; Geochemical analysis